Improving Creativity Through Playdough Games for Children - Ni’mah, Alfiyatun; Fachrurrazi, Ahmad (Academia Publication, 2025)
This study is based on the fact that the creativity of children in group A at Mawar Merah Kindergarten, Sidobogem Village, Sugio, Lamongan, is still underdeveloped. Observations show that during skill-building activities, children tend to be less careful and less persistent in their work, resulting in less neat and less optimal results. One of the causes is the teaching approach applied by teachers, which focuses more on creativity materials with a low level of difficulty. As a result, children are less accustomed to facing new challenges. In addition, teachers also rarely apply creativity learning through games, which have the potential to enhance children's development. Based on these phenomena, the research question in this study is: “How can we improve the creativity of children in group A at Mawar Merah Kindergarten through playdough games?” The purpose of this study is to improve children's creativity in the classroom by using playdough games in the 2024/2025 academic year. This study involved nine children from group A of Mawar Merah Kindergarten. The data collection methods used included observation and documentation. The results of the analysis showed that there was an effect on increasing creativity through playdough games in group A children at Mawar Merah Kindergarten, Sidobogem Village, Sugio District, Lamongan Regency, in the 2024/2025 academic year.